Предмет: Алгебра,
автор: Дамир808
Докажите, что значение выражения (3x-1)(4x-3)-(3x+1)(4x+3)+26x+2 не зависит от значений x.
Ответы
Автор ответа:
0
12x^2 - 9x - 4x + 3 - ( 12x^2 + 9x + 4x + 3 ) + 26x + 2 =
= 12x^2 - 9x - 4x + 3 - 12x^2 - 9x - 4x - 3 + 26x + 2 = - 13x - 13x + 26x + 2 =
= - 26x + 26x + 2 = 2 - не зависит от значений x.
= 12x^2 - 9x - 4x + 3 - 12x^2 - 9x - 4x - 3 + 26x + 2 = - 13x - 13x + 26x + 2 =
= - 26x + 26x + 2 = 2 - не зависит от значений x.
Автор ответа:
0
что означает знак ^
Похожие вопросы
Предмет: Геометрия,
автор: adilzhirenovo32
Предмет: Математика,
автор: tsyantsin
Предмет: Литература,
автор: angelinakocura329
Предмет: История,
автор: kamynin1976
Предмет: Алгебра,
автор: Anton123490